Below or all the way to the peak? Oxygen uptake efficiency slope as the index of cardiorespiratory response to exercise—the NOODLE study - Kasiak, Przemysław; Kowalski, Tomasz; Rębiś, Kinga; Klusiewicz, Andrzej; Starczewski, Michał; Ładyga, Maria; Wiecha, Szczepan; Barylski, Marcin; Poliwczak, Adam Rafał; Wierzbiński, Piotr; Mamcarz, Artur; Śliż, Daniel (Frontiers in Physiology, 2024)
The ratio of oxygen uptake (VO2) to minute ventilation (VE) is described as the Oxygen Uptake Efficiency Slope (OUES). OUES has been suggested as a valuable submaximal cardiorespiratory index, however, its characteristics in endurance athletes remain unknown. In this study we: (a) investigated OUES between different time intervals, (b) assessed their prediction power for VO2peak, and (c) derived new prediction equations for OUES tailored for well-trained individuals.77 males (age=21.4±4.8 yrs.; BMI=22.1±1.6 kg•m -2 ; peak oxygen uptake=4.40±0.64 L•min -1 ) and 63 females (age=23.4±4.3 yrs.; BMI=23.1±1.6 kg•m -2 ; peak oxygen uptake=3.21±0.48 L•min -1 ) underwent cycling cardiopulmonary exercise test. OUES was measured at 75%, 90%, and 100% of exercise duration. Prediction power and new models were derived with the Multiple Linear Regression.In males, OUES [mL•min -1 /L•min -1 ] from 75%= 4.53±0.90, from 90%= 4.52±0.91 and from 100%= 4.41±0.87. In females, OUES [mL•min -1 /L•min -1 ] from 75%= 3.50±0.65, from 90%= 3.49±0.62 and from 100%= 3.41±0.58. OUES did not differ between time intervals in males (p=0.65) and females (p=0.69). OUES strongly predicts peak VO2, independently from measuring interval (β= 0.71-0.80; R 2 = 0.50-0.63). The prediction model designed for elite athletes was: OUES [mL•min -1 /L•min -1 ]= -1.54 + 2.99 • BSA [m 2 ] -0.0014 • (age [in years] • sex [1=male, 2=female]) (R 2 = 0.36).OUES enables accurate prediction of peak cardiorespiratory fitness in elite endurance athletes. OUES is a feasible alternative to maximal exercise testing. A new prediction equation should be used for highly trained individuals. Physicians should understand OUES physiology to properly assess cardiorespiratory response to exercise in athletic cohorts.